TONGUE—A NEWER BIOMETRIC: An Observational Study - Vishnu Rajendran; Arul Jothi Murugan; Anuradha Ganesan (Journal of Indian Academy of Oral Medicine and Radiology)
Background: The tongue is an integral internal organ which is shielded from its outside environment within the oral cavity. Every individual has a distinct morphology and surface characteristics that can be employed for personal identification. Aim: To analyze the morphological alterations on the dorsum of the tongue using digital images and determine their significance for person identification. Objectives: To clinically examine the dorsum of the tongue and take digital photographs. To observe the morphological variations seen on the tongue surface. To assess the usefulness of observed morphological variations in personal identification. Materials and Methods: Our study included 104 participants, aged 21–41 years, reporting to the Department of Oral Medicine and Radiology for various concerns. All the participants were examined visually; to assess various morphological patterns of the tongue, digital images of the dorsum of the tongue were taken. Results: Statistical analysis showed that U-shaped tongue was predominant in both sexes, and smooth borders were more common in females (82.7%) than males (63.5%). Male participants showed single or multiple fissures more commonly. Conclusion: Considering the uniqueness, genetic independence, and simple procedure, tongue print can be considered biometric identification along with other forensic identification techniques.